2021
DOI: 10.1002/ccd.29953
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the polymer‐free and polymer‐coated drug‐eluting stents in patients undergoing percutaneous coronary intervention

Abstract: Introduction:The relative safety and efficacy of polymer-free (PF) versus polymercoated (PC) drug-eluting stents (DES) in patients with angina or acute coronary syndrome (ACS) undergoing percutaneous coronary intervention has received limited study.Method: Digital databases were queried to identify relevant studies. Major adverse cardiovascular events (MACE) and secondary outcomes were compared using a random effect model to calculate unadjusted odds ratios (OR).Results: A total of 28 studies consisting of 23,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Numerous studies have examined the causes of these post-DES implant delayed events and found that stent features and fundamental health factors, such as older age, diabetes, and acute manifestations, may operate as independent risk factors of late stent consequences. Ullah et al [ 43 ] suggested that patients who received either PF-DES or PC-DES appeared to have a similar risk of major adverse cardiovascular events (MACEs), strokes, MI, stent thrombosis, and the need for target lesion and vessel revascularization (TLR and TVR) [ 43 ]. Their overall results were consistent across multiple subgroup analyses based on the length of follow-up (one month to 10 years), the presence of diabetes mellitus (DM), the clinical presentation (angina vs. STEMI), and the kind of drug-eluting PF stents used.…”
Section: Reviewmentioning
confidence: 99%
“…Numerous studies have examined the causes of these post-DES implant delayed events and found that stent features and fundamental health factors, such as older age, diabetes, and acute manifestations, may operate as independent risk factors of late stent consequences. Ullah et al [ 43 ] suggested that patients who received either PF-DES or PC-DES appeared to have a similar risk of major adverse cardiovascular events (MACEs), strokes, MI, stent thrombosis, and the need for target lesion and vessel revascularization (TLR and TVR) [ 43 ]. Their overall results were consistent across multiple subgroup analyses based on the length of follow-up (one month to 10 years), the presence of diabetes mellitus (DM), the clinical presentation (angina vs. STEMI), and the kind of drug-eluting PF stents used.…”
Section: Reviewmentioning
confidence: 99%